1988
DOI: 10.1002/app.1988.070350105
|View full text |Cite
|
Sign up to set email alerts
|

The non‐Fickian diffusion of deterrents into a nitrocellulose‐based propellant

Abstract: SynopsisThe diffusion of solutions of ethyl centralite (EC), dibutylphthalate (DBP), an-. dinitrotoluene (DNT) into a nitrocellulose (NC) propellant is investigated. DBP and EC penetrate the propellant in a way consistent with Case I1 diffusion. The diffusion of DNT solutions is Fickian. The apparent activation energy for Case I1 diffusion is 62 kJ/mol for DBP and 66 kJ/mol for EC.Changes to coating solvent polarity have little effect on DNT and DBP penetration and merely alter the rate, not the mechanism, of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The observed non-Fickian concentration profiles were attributed to Case I1 diffusion occuring due to swelling of the outer layer of the propellant grains under the influence of the deterrent and coating solvent (24). This seems to be plausible as it is known that most deterrents and in particular the coating solvents are good plasticizers and will efficiently swell or gelatinize the nitrocellulose matrix.…”
Section: Difsusion During the Deterring Processmentioning
confidence: 91%
See 1 more Smart Citation
“…The observed non-Fickian concentration profiles were attributed to Case I1 diffusion occuring due to swelling of the outer layer of the propellant grains under the influence of the deterrent and coating solvent (24). This seems to be plausible as it is known that most deterrents and in particular the coating solvents are good plasticizers and will efficiently swell or gelatinize the nitrocellulose matrix.…”
Section: Difsusion During the Deterring Processmentioning
confidence: 91%
“…According to this model, the deterrent moves into the propellant by diffusion and molecules are withdrawn from the flow by hydrogen bonding. However, Winkler et al (24) demonstrated that the "diffusion with interaction" model is inadequate in describing the anomalous concentration profiles as well as the observed solvent effects. It was pointed out that a dipolar interaction (such as hydrogen bonding) between nitrocellulose matrix and deterrent would in fact reduce the value of the diffusion coefficient but would maintain the exponential shape of the concentration profilethe diffusion would still be F i~k i a n (~~>~~) .…”
Section: Difsusion During the Deterring Processmentioning
confidence: 99%
“…To combine nEMs with the MWCNT paper electrode, suitable binders are required. Nitrocellulose (NC) is suggested as one of the promising binders because it is known to be a highly flammable polymer to incorporate with nEMs for promoting the combustion process in modern gunpowder and propellants. In addition, NC can be easily dissolved in organic solvents and is hydrophobic, owing to which it is frequently used as an industrial polymer for coating plastics, membranes, and wooden materials. …”
Section: Introductionmentioning
confidence: 99%